Multiparametric analysis of the specific immune response against SARS-CoV-2 - Vránová, Lucie; Poláková, Ingrid; Vaníková, Šárka; Saláková, Martina; Musil, Jan; Vaníčková, Marie; Vencálek, Ondřej; Holub, Michal; Bohoněk, Miloš; Řezáč, David; Dresler, Jiří; Tachezy, Ruth; et al. (Infectious diseases (London, England), 2024)
BACKGROUND: SARS-CoV-2, which causes COVID-19, has killed more than 7 million people worldwide. Understanding the development of postinfectious and postvaccination immune responses is necessary for effective treatment and the introduction of appropriate antipandemic measures. OBJECTIVES: We analysed humoral and cell-mediated anti-SARS-CoV-2 immune responses to spike (S), nucleocapsid (N), membrane (M), and open reading frame (O) proteins in individuals collected up to 1.5 years after COVID-19 onset and evaluated immune memory. METHODS: Peripheral blood mononuclear cells and serum were collected from patients after COVID-19. Sampling was performed in two rounds: 3-6 months after infection and after another year. Most of the patients were vaccinated between samplings. SARS-CoV-2-seronegative donors served as controls. ELISpot assays were used to detect SARS-CoV-2-specific T and B cells using peptide pools (S, NMO) or recombinant proteins (rS, rN), respectively. A CEF peptide pool consisting of selected viral epitopes was applied to assess the antiviral T-cell response. SARS-CoV-2-specific antibodies were detected via ELISA and a surrogate virus neutralisation assay. RESULTS: We confirmed that SARS-CoV-2 infection induces the establishment of long-term memory IgG+ B cells and memory T cells. We also found that vaccination enhanced the levels of anti-S memory B and T cells. Multivariate comparison also revealed the benefit of repeated vaccination. Interestingly, the T-cell response to CEF was lower in patients than in controls. CONCLUSION: This study supports the importance of repeated vaccination for enhancing immunity and suggests a possible long-term perturbation of the overall antiviral immune response caused by SARS-CoV-2 infection.
Keywords: dospělí; COVID-19; protilátky virové; humorální imunita; Humans; ELISpot; Enzyme-Linked Immunospot Assay; lidé středního věku; Middle Aged; Immunity, Cellular; Antibodies, Viral; leukocyty mononukleární; Spike Glycoprotein, Coronavirus; antibody; virus neutralisation assay; glykoprotein S, koronavirus; mužské pohlaví; Immunity, Humoral; Leukocytes, Mononuclear; B-Lymphocytes; Adult; COVID-19 Vaccines; T-Lymphocytes; imunologická paměť; buněčná imunita; immune memory; ženské pohlaví; T-lymfocyty; ELISPOT; B-lymfocyty; vakcíny proti COVID-19; lidé; Immunologic Memory; SARS-CoV-2; adaptive immunity; Aged; senioři; Male; Female